SQL for MySQL : a beginner's tutorial - Darmawikarta, Djoni (Brainy Software, 2014)
This introduction to SQL for MySQL begins by discussing exactly how data is stored and maintained in a relational database, familiarizing readers with SQL INSERT, UPDATE, and DELETE statements. The guide then discusses how to construct basic queries, choose an appropriate output, and how to create and use groups. Readers will also learn how to use joins to query data from multiple tables, how to create predefined views that can be stored in a database, and how to utilize the metadata of a database. Appendices round out the book, covering the various indexing techniques available in MySQL and discussing how to install MySQL Community Edition and list the MySQL built-in data types.